SIKAP KEPEMIMPINAN DAN PERCAYA DIRI SEBAGAI MANIFESTASI KECERDASAN EMOSIONAL ANAK USIA DINI - Wardani, Herfina; Zalfa Nur Adibah, Farah; Sugiyarti, Dian (PGSD STKIP PGRI Pacitan, 2024)
Emotional intelligence can be broadly interpreted as a skill or ability that enables awareness of one's own emotional state and the emotions of others as well as the capacity to use and manage emotions in order to positively influence role performance. This research aims to find out the importance of growing emotional intelligence in early childhood in terms of leadership and self-confidence. The research method used is a phenomenological qualitative method with data collection techniques using interviews and observations conducted at TK IT Muadz bin Jabal Kota Gede Yogyakarta. The subjects of this study were children aged 5-6 years. The results of the study show that there is an attitude of leadership and self-confidence as an indicator of children's emotional intelligence. This is shown by the child being able to lead his friends in class to determine the rules for playing activities and the child feels proud when he is able to memorize letters in the Al Quran and the child also dares to show his abilities to others. In practice, leadership and self-confidence are fostered by setting an example in a mutually supportive environment.